All things in common : a Canadian family and its island utopia - Brouwer, Ruth Compton (Canadian social history series., 2021)
"In the first decade of the twentieth century, a few closely related families established a utopian community in Canada's smallest province. Known officially as B. Compton Limited but described by a journalist in 1935 as "Prince Edward Island's unique 'brotherly love' community," this utopia owed its longevity to the cohesion provided by its communal organization, dense kin ties, and long-held millenarianism - and to a decidedly pragmatic approach to business. All Things in Common demonstrates how "un-utopian" such a community could be while problematizing the contention that the inevitable end of all utopian experiments is a full-blown dystopia. Beginning with a compelling backstory and locating the Compton community in the historiography of North American utopias, the author goes on to explore the community's business endeavours, its religious, familial, and transgressive aspects, and its brief period of international fame before assessing the factors that led to its dissolution in 1947. Providing a strong narrative framework, All Things in Common draws on rich family and archival records and diverse secondary sources, concluding with a consideration of the community's legacy for its alumni and their descendants."--